1997
DOI: 10.1161/01.atv.17.3.445
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized LDL Mediates the Release of Fibroblast Growth Factor-1

Abstract: Fibroblast growth factor-1 (FGF-1) and lipoproteins play an important role in atherogenesis. In the present study, we explored a possible mechanism by which abnormal lipid metabolism could be linked to the proliferative aspects of the disease. We tested oxidized LDL (oxLDL) as a possible pathophysiological mediator of the release of FGF-1, using FGF-1-transfected mouse NIH 3T3 cells and FGF-1-transfected rabbit smooth muscle cells, and compared it with the release caused by elevated temperature. Immunoblot ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 57 publications
1
24
0
Order By: Relevance
“…Interestingly, the immunoreactivity of VEGFR-1 was colocalized in atheromatous plaques and observed in foam cell-rich regions adjacent to the lipid core or the basal regions of plaque consisting predominantly of VSMCs. Ananyeva et al (1997) recently demonstrated that ox-LDL induced the release of aFGF from aFGF-transfected VSMCs. VEGF receptor (flt-1) expression in monocyte and VSMCs has recently been confirmed; this receptor mediates chemotaxis and tissue factor production associated with up-regulation of MMPs to contribute to the lateral expansion of new blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the immunoreactivity of VEGFR-1 was colocalized in atheromatous plaques and observed in foam cell-rich regions adjacent to the lipid core or the basal regions of plaque consisting predominantly of VSMCs. Ananyeva et al (1997) recently demonstrated that ox-LDL induced the release of aFGF from aFGF-transfected VSMCs. VEGF receptor (flt-1) expression in monocyte and VSMCs has recently been confirmed; this receptor mediates chemotaxis and tissue factor production associated with up-regulation of MMPs to contribute to the lateral expansion of new blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…2 In this paper we use phosphorylation of aFGF as a measure of translocation to the cytosol and nucleus, since these are the only places in the cell where protein kinase C is known to exist. In untransfected COS cells, which express little or no FGFR, aFGF is not translocated to the cytosol and nucleus, and hence, it is also not phosphorylated.…”
Section: S]methionine-labeled Afgf (Upper Panel) As Well As Farnesylamentioning
confidence: 99%
“…Acidic fibroblast growth factor (aFGF) 1 is considered to be involved in several important physiological and pathological processes, such as angiogenesis, wound healing (1), and atheromatosis (2)(3)(4)(5)(6). In cell cultures it can stimulate growth, cell migration, and differentiation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, FGF1 export through exocytotic fusion of secretory vesicles with the cell membrane is unlikely. FGF1 is secreted from cells upon stress stimulation such as heat shock [14], hypoxia [17], serum starvation [18], and treatment with oxidized LDL [19]. The availability of free intracellular copper ions is necessary for FGF1 release, and in vitro data suggest the formation of a copper-and stress-dependent multiprotein export complex [20], which contains the calcium-binding proteins, S100A13 and p40 Syt1 [21,22].…”
Section: Introductionmentioning
confidence: 99%